Utilização de métodos combinados para obtenção de mamão formosa (carica papaya) seco - Garcia, Carolina Castilho; Canizares, Diego [UNESP]; Silva, Keila de Souza [UNESP]; Darros-Barbosa, Roger [UNESP]; Mauro, Maria Aparecida [UNESP] (Centro Pesquisa Processamento Alimentos, 2012)
COMBINED METHODS TO OBTAIN DRIED PAPAYA of FORMOSA CULTIVAR (Carica papaya) The aim of this work was to evaluate the influence of blanching in hot water, osmotic dehydration in sucrose solution and pectin coating on color and water activity of papaya slices after convective drying. on the first experiments, the influence of concentration and time of dehydration on color changes and water activity of fresh and blanched papaya slices was evaluated based on a factorial design. It was not verified significant color changes at the studied ranges. An expression for the water activity of osmotically dehydrated blanched samples was found. Then, the influences of blanching, osmotic dehydration, edible coating and combinations among these pre-treatments on color and water activity were evaluated after convective drying of papaya slices. Blanching was not an advantageous pre-treatment to maintain color and reduce water activity of dried fruits. Osmotically dehydrated fresh samples with or without coating presented the best results.
Combined methods to obtain dried papaya of formosa cultivar (carica papaya)
Keywords: Osmotic dehydration; Blanching; EDIBLE FILMS; Drying; Papaya